Water deficit stress tolerance in maize conferred by expression of an isopentenyltransferase (IPT) gene driven by a stress- and maturation-induced promoter - Décima Oneto, Cecilia Andrea (2016)
Senescence can be delayed in transgenic plants overexpressing the enzyme isopentenyltransferase (IPT) due to stress-induced increased levels of endogenous cytokinins. This trait leads to sustained photosynthetic activity and improved tolerance to abiotic stress. The aim of this study was to generate and characterize transgenic plants of maize (Zea mays L.) transformed with the IPT gene sequence under the regulation of SARK promoter (protein kinase receptor-associated senescence). Three independent transgenic events and their segregating null controls were evaluated in two watering regimes (WW: well watered; WD: water deficit) imposed for two weeks around anthesis. Our results show that the WD treatment induced IPT expression with the concomitant increase in cytokinin levels, which prolonged the persistence of total green leaf area, and maintained normal photosynthetic rate and stomatal conductance. These trends were accompanied by a minor decrease in number of grains per plant, individual grain weight and plant grain yield as compared to WW plants. Plants expressing the IPT gene under WD had PGR, anthesis and silking dates and biomass levels similar to WW plants. Our results demonstrate that expression of the IPT gene under the regulation of the SARK promoter helps improve productivity under WD conditions in C4 plants like maize.